Highly efficient rDNA‐mediated multicopy integration based on the dynamic balance of rDNA in Saccharomyces cerevisiae - Huihui Zheng (Microbial Biotechnology, 2022)
Summary Engineered Saccharomyces cerevisiae strains are good cell factories, and developing additional genetic manipulation tools will accelerate construction of metabolically engineered strains. Highly repetitive rDNA sequence is one of two main sites typically used for multicopy integration of genes. Here, we developed a simple and high‐efficiency strategy for rDNA‐mediated multicopy gene integration based on the dynamic balance of rDNA in S. cerevisiae. rDNA copy number was decreased by pre‐treatment with hydroxyurea (HU). Then, heterologous genes were integrated into the rDNA sequence. The copy number of the integrated heterologous genes increased along with restoration of the copy number of rDNA. Our results demonstrated that HU pre‐treatment doubled the number of integrated gene copies; moreover, compared with removing HU stress during transformation, removing HU stress after selection of transformants had a higher probability of resulting in transformants with high‐copy integrated genes. Finally, we integrated 18.0 copies of the xylose isomerase gene into the S. cerevisiae genome in a single step. This novel rDNA‐mediated multicopy genome integration strategy provides a convenient and efficient tool for further metabolic engineering of S. cerevisiae.